191k views
4 votes
What is the simplified form of the expression 3(7/5x+4)-2(3/2-5/4x)?

User Gthuo
by
5.2k points

2 Answers

4 votes

Answer:

Explanation:

distribute the first part of each term

(21/5x+12)+(-3+5/2x)

combine the xs and the numbers

9+6.7x

User Janx
by
4.3k points
5 votes

For this case we must simplify the following expression:


3((7)/(5)x+4)-2((3)/(2)-(5)/(4)x)=\\(3*7)/(5)x+ 3*4-(2*3)/(2) +(2*5)/(4)x=\\(21)/(5)x +12-(6)/(2) +(10)/(4)x=\\(21)/(5)x +12-3+ (10)/(4)x=

We add similar terms:


(21)/(5)x+ (10)/(4)x+ 9=\\((21)/(5) +(10)/(4))x +9=\\(67)/(10)x +9

ANswer:


(67)/(10)x+9

User Jeff Baranski
by
5.2k points